Empowerment of Coastal Communities Through Sea Fish Processing in Improving The Economy of The Bumi Mangrove Forest Farmers and Fishermen Group Percut Village, Deli Serdang Regency - Herlin Munthe; Rafida Khairani; Purnama Yanti Purba (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The Bumi Mangrove Forest and Fishermen Farmers Group is a group that has been established since 2019 consisting of 38 members in Percut Village, Percut Sei Tuan District, Deli Serdang Regency who are still at the poverty line. The purpose of implementing this program is to invite and empower the Bumi Mangrove fishermen group in improving business management and production skills to make fish crackers, digital marketing training, and mentoring the making of crackers for mothers of the Bumi Mangrove fishermen group in Percut Village, Percut Sei Tuan District, Deli Serdang Regency. The method used is to provide assistance and facilitate the learning of making fish crackers for the Bumi Mangrove Fishermen Group as a business for mothers who still lack access to learning how to make fish crackers so that community knowledge about business management can continue to grow and educate digital marketing as a means of promotion and finding new markets. This program has been implemented for two days, namely on September 26-27, 2024. On September 26, 2024, there was a ceremonial handover of fish cracker processing equipment and materials by the implementation team to representatives of the Percut Sei Tuan Village Head, Farmers and Fishermen Groups, implementation of Production Management and Business Management Workshops delivered by Mrs. Purnama Yanti Purba and workshops digital marketing training delivered by Mrs. Rafida Khairani. Furthermore, on September 27, 2024, assistance in fish cracker processing training activities was carried out by Ms. Naziya. The results of this implementation are that all fishermen group mothers can implement the knowledge they have learned as evidenced by the increase in the quality and quantity of processed crackers from 30 kg to 60 kg per month and have Bumi Mangrove social media account.